Reflexivity and critical pedagogy - Ryan, Anne, 1953-; Walsh, Tony, 1951- (International issues in adult education, 2018)
Reflexivity and Critical Pedagogy highlights the essential nature of reflexivity in creating sites for transformative possibilities in education. The book argues that seemingly intractable epistemological inequalities are embedded within educational structures and processes and also contends that perspectives which define knowledge as a unitary truth are essentially inadequate to address current global problems. Further, it argues that people and ideas traditionally positioned outside the academy are vital to developing more effective educational interventions. This volume stresses the influence of dominant societal discourses in creating and sustaining particular and limited definitions of knowledge. It also explores their power in delineating acceptable processes of knowledge dissemination. These discourses, whether consciously or otherwise, indwell teachers, learners and policy-makers as well as educational structures and organisations. It proposes reflexivity as the key component needed to combat such forces and one that is an essential ingredient in critical pedagogy.